Becoming a teacher: tracing changes in pre-service English as a foreign language teachers' sense of efficacy - Yuksel, H. Gulru (EDUCATION ASSOC SOUTH AFRICA, 2014)
This longitudinal study aimed to trace changes in Turkish pre-service English as a foreign language teachers' self-efficacy over a year, and to detect possible sources of information influencing their efficacy. Utilizing concurrent mixed model design of Creswell (2003) both qualitative and quantitative data was collected. A total of 40 pre-service teachers participated in the study. Findings indicated that pre-service English language teachers' efficacy changed significantly over time. We also found that pre-service teachers seem to depend more on enactive mastery experience and social persuasion than on vicarious experience and affective state as sources of information. Based on our findings, measures are suggested on how to support pre-service teachers to improve their sense of efficacy. Implications for research on teaching and teacher education are discussed.
Keywords: pre-service teachers; school observation; sources of teacher efficacy; student teaching; teachers' sense of efficacy; SELF-EFFICACY; BELIEFS; SCHOOLS; Education & Educational Research